Accumbens dopamine D2 receptors increase motivation by decreasing inhibitory transmission to the ventral pallidum - Eduardo F. Gallo (Nature Portfolio, 2018)
Dopamine D2 receptor activity in the nucleus accumbens is associated with regulation of motivated responding. Here the authors show that overexpression of D2 receptors specifically in ventral striatal projection neurons leads to an increase in the willingness to work by reducing inhibitory transmission to ventral pallidal neurons.